85.6k views
1 vote
X=(y)/(y-3) make y the subject

User Ahmacleod
by
5.2k points

1 Answer

5 votes

Answer:


\displaystyle y=(3x)/(x-1)

Explanation:

Solving Equations

We have the expression:


\displaystyle x=(y)/(y-3)

And it's required to make y the subject.

It can be done by isolating y on the left side of the equation and the rest of the expression on the right side.

The first step is removing the denominator by multiplying both sides by y-3:


\displaystyle (y-3)x=(y-3)(y)/(y-3)

Simplifying the right side:


\displaystyle (y-3)x=y

Remove the parentheses:


yx-3x=y

Move the y's to the left side and the rest of the expression to the right side:


yx-y=3x

Factor out y:


y(x-1)=3x

Divide by x-1:


\mathbf{\displaystyle y=(3x)/(x-1)}

User CodyKL
by
5.5k points